Optical coherence tomography characteristics of group 2A idiopathic parafoveal telangiectasis (2007)
PURPOSE: To describe the optical coherence tomography (OCT) characteristics of patients with group 2A idiopathic parafoveal telangiectasis (IPFT) and to correlate them with biomicroscopic and fluorescein angiographic (FA) findings based on Gass and Blodi staging classification for group 2A IPFT. METHODS: Fifty-two eyes of 26 consecutive patients with IPFT underwent biomicroscopic fundus examination, color fundus photography, FA, and OCT. Main outcome measures were OCT characteristics and their correlation with biomicroscopy and FA. RESULTS: The most common OCT findings that help differentiate between stages in group 2A IPFT are 1) highly reflective dots in the inner retina that correspond with microvessels seen by FA in Stage 1 (5 eyes [62.5%]); 2) the presence of hyporeflective intraretinal spaces in the absence of retinal thickening and highly reflective dots in the retina in Stage 2 (9 [81.8%] and 10 eyes [90.9%], respectively); 3) in Stage 3, both outer and inner retina exhibit areas of similar high reflectivity. In addition, the retinal pigment epithelium (RPE)/choriocapillaris complex is thickened or disrupted as evidenced by an area of high reflectivity (13 eyes [81.2%]); 4) a highly reflective area nasal or temporal to the fovea in the inner or outer retinal layers in Stage 4 suggesting RPE proliferation and migration (13 eyes [100%]); and 5) a fusiform thickening and duplication of the highly reflective RPE/choriocapillaris complex corresponding to choroidal neovascularization in Stage 5 (4 eyes [100%]). Our OCT characteristics correlated well with biomicroscopic and FA findings for Stages 4 and 5. However, the hyporeflective spaces that are evident on OCT could not be seen clinically at the slit lamp or on FA. In addition, our OCT findings on eyes with group 2A IPFT Stage 3 have not, to our knowledge, been previously described. CONCLUSIONS: Optical coherence tomography findings in group 2A IPFT were characteristic for each stage and may be helpful in making the diagnosis as well as defining the anatomical staging proposed by Gass and Blodi. Optical coherence tomography complements biomicroscopic and FA findings in the evaluation of group 2A IPFT. © The Ophthalmic Communications Society, Inc.